Moving beyond linear food chains: trait-mediated indirect interactions in a rocky intertidal food web - Trussell, Geoffrey C. (Proc Biol Sci, 2017)
In simple, linear food chains, top predators can have positive indirect effects on basal resources by causing changes in the traits (e.g. behaviour, feeding rates) of intermediate consumers. Although less is known about trait-mediated indirect interactions (TMIIs) in more complex food webs, it has been suggested that such complexity dampens trophic cascades. We examined TMIIs between a predatory crab (Carcinus maenas) and two ecologically important basal resources, fucoid algae (Ascophyllum nodosum) and barnacles (Semibalanus balanoides), which are consumed by herbivorous (Littorina littorea) and carnivorous (Nucella lapillus) snails, respectively. Because crab predation risk suppresses snail feeding rates, we hypothesized that crabs would also shape direct and indirect interactions among the multiple consumers and resources. We found that the magnitude of TMIIs between the crab and each resource depended on the suite of intermediate consumers present in the food web. Carnivorous snails (Nucella) transmitted TMIIs between crabs and barnacles. However, crab–algae TMIIs were transmitted by both herbivorous (Littorina) and carnivorous (Nucella) snails, and these TMIIs were additive. By causing Nucella to consume fewer barnacles, crab predation risk allowed fucoids that had settled on or between barnacles to remain in the community. Hence, positive interactions between barnacles and algae caused crab–algae TMIIs to be strongest when both consumers were present. Studies of TMIIs in more realistic, reticulate food webs will be necessary for a more complete understanding of how predation risk shapes community dynamics.